The Upregulation of IL-1β Induced by Cisplatin Triggers PI3K/AKT/MMP9 Pathway in Pericytes Mediating the Leakage of the Blood Labyrinth Barrier - Yu M; Jiang WJ; Yu M; Zhou Z; Wang M; Li L (Journal of Inflammation Research)
Miao Yu,1,2,* Wen-Jun Jiang,3,4,* Meng Yu,1 Zan Zhou,1,2 Min Wang,1 Li Li1 1Department of Physiology, Medical College of Jiaxing University, Jiaxing, Zhejiang, 314000, People’s Republic of China; 2Department of Physiology, Medical College of Shihezi University, Shihezi, Xinjiang, 832000, People’s Republic of China; 3The Second People’s Hospital of Li Shui, Li Shui, Zhejiang, 323000, People’s Republic of China; 4Department of Physiology, Zhejiang Chinese Medical University, Hangzhou, Zhejiang, 310051, People’s Republic of China*These authors contributed equally to this workCorrespondence: Min Wang, Email wangmin3826@zjxu.edu.cn Li Li, Email lily7588@163.comBackground: Blood–labyrinth barrier (BLB) damage has been recognized as a key mechanism underlying cisplatin (CDDP)-induced hearing loss. Inflammation within the cochlea, triggered by CDDP, is a key pathological response. However, the relationship between CDDP-induced inflammation and BLB dysfunction remains elusive.Materials and Methods: In vivo and in vitro BLB models were used to explore the inflammatory mechanisms underlying CDDP ototoxicity. C57BL/6J mice were treated with CDDP and IL-1β levels, BLB permeability, and hearing thresholds were assessed using ELISA, histological staining, ABR test and BLB leakage tests. In vitro BLB models, the effect of IL-1β on MMP9 expression, PI3K-AKT pathway activation, and endothelial barrier permeability were examined via Western blot, TEER value test, and FITC extraction analysis. In addition, inhibitors of IL-1β, MMP9, and PI3K-AKT were used to analyze the specific mechanisms.Results: After CDDP treatment, IL-1β upregulation in the stria vascularis disrupted tight junctions, increased BLB permeability, and led to hearing loss. Notably, IL-1β inhibition with AS101 attenuated hearing threshold elevation and BLB damage in CDDP-treated mice. Mechanistically, CDDP triggered IL-1β release from endothelial cells. IL-1β promoted MMP9 secretion from pericytes via the PI3K/AKT pathway, leading to disruption of tight junctions. Both MMP9 and PI3K-AKT inhibitors abrogated IL-1β-induced changes.Conclusion: Our findings suggest that CDDP initiates a cascade of events starting with IL-1β release from endothelial cells. This release triggers the activation of PI3K/AKT pathway and upregulation of MMP9 expression in pericytes, which increases BLB permeability and leds to hearing loss. IL-1β and the PI3K-AKT pathway are promising therapeutic targets,offering hope for patients with CDDP-induced hearing loss. Keywords: cisplatin, BLB, IL-1β, MMP9, PI3K/AKT pathway